Decreased platelet number in multiple sclerosis during alemtuzumab infusion: a common, transient and clinically silent phenomenon. (13th December 2017) - Puthenparampil, Marco; Rinaldi, Francesca; Federle, Lisa; Cazzola, Chiara; Perini, Paola; Gallo, Paolo
Background: The cause and clinical significance of the transient decrease in platelet (PLT) count observed in relapsing remitting multiple sclerosis (RRMS) during alemtuzumab administration remain undefined. The aim of this study was to analyse the kinetics and clinical relevance of early onset thrombocytopaenia in alemtuzumab-treated RRMS. Methods: A total of 26 patients with RRMS were included in a longitudinal study. Blood samples were collected immediately before the first alemtuzumab infusion (D0), and after 3 days (D3), 28 days (D28) and 49 days (D49). PLT, red blood cell (RC), leucocyte and lymphocyte counts, haemoglobin (Hb) concentration and haematocrit (Htc) were measured. Patients with MS were clinically evaluated every day of drug infusion and then at D28 and D49 to verify the presence of signs or symptoms suggestive of thrombocytopaenia. Results: PLT number significantly decreased at D3 ( p < 0.005) and was associated with a decrease in RC count ( r : 0.53, p < 0.01), Hb ( r : 0.42, p = 0.05) and Htc ( r : 0.53, p < 0.01). A progressive reversion of PLT number to normal values was observed at D28 and D49. A mild thrombocytopaenia was observed in 12 patients (46.2%), 8 of which (66.6%) had PLT nadir values at D3, and 4 (33.3%) at D28. No sign or symptom suggestive of thrombocytopaenia was observed. A strong correlation between pretreatment and nadir PTL counts ( r : 0.59, p < 0.005) was observed; indeed, mild thrombocytopaenia was observed more frequently in these patients with a baseline PTL count lower than 230 × 10 9 /L (83.3% versus 42.9%, p < 0.05). Conclusions: The early PLT decrease in alemtuzumab-treated patients is transient, mild, not associated with clinically relevant events and is probably related to the cytokine-released syndrome. Notwithstanding this, our findings suggest the opportunity for PLT monitoring during infusion and in the following 2 months, since a decrease in PLT count may occur.